How far have the principles articulated by the House of Lords in Salomon V.A. Salomon & sons ltd [1897] ac 22 been developed since the decision? To what extent does the current approach accord with modern business practice? - Mekhrabi, K. (KSU Publ., 2014)
This essay examines evolution of corporate legal personality and limited liability concepts and their relevance to modern business practice. It will also deal with issues of when a company's legal personality is ignored and when the veil is lifted. It is not merely about disregarding the corporate personality, but also about imposing just and reasonable limitations on the exercise of the privilege of independent capacity.
Лордтар палатасымен қалыптастырылған қағидалардың дамуы Salomon V.A. Salomon & sons ltd [1897] ac 22 жəне оларды қазіргі кездегі іскерлік тəжірибеде қолдану мүмкіндігі
Развитие принципов, сформулированных палатой лордов в Salomon V.A. Salomon & sons ltd [1897] ac 22, и возможность их применения в современной деловой практике
Keywords: corporate law; corporate personality; corporation; legal entity; enterprise; limited liability principles; Solomon principles